Quality of Life and Associated Factors Among Adult Cancer Patients Undergoing Chemotherapy Treatment at Amhara National, Regional State, Ethiopia, 2021 - Ahmed Nuru Muhamed MSc; Sitotaw Kerie Bogale MSc; Henok Biresaw Netere MSc (SAGE Publishing, 2023)
Background In cancer, quality of life (QoL) is an important patient-reported metric; evaluating how patients feel physically and emotionally while fighting the disease could lead to better treatment. Despite its therapeutic effects, chemotherapy treatment causes a plethora of side effects that can affect QoL. Factors affecting the QoL of cancer patients undergoing chemotherapy treatment in Ethiopia have not been thoroughly investigated. As a result, this study assesses QoL and associated characteristics among adult cancer patients receiving chemotherapy at Amhara Region, Ethiopia in 2021. Martials and Methods From February 15 to May 15, 2021, an institutional based cross-sectional study was done in Amhara region. Three hundred fourteen patients were included in the study. The data was gathered using Amharic version of European organization for research and treatment of cancer quality of life questionnaire (EORTC QLQ C-30) through a face-to-face interview. Epi Data 4.6 was used to enter the data, which was then exported to SPSS version 23 for statistical analysis. Multivariable logistic regression analysis was used to determine the relationship between independent and dependent variables. The statistical significance was determined by a p -value of less than .05. Result Cancer patients in Amhara Region had a 44.32 average QoL. Emotional functioning AOR 1.01 (1.0-1.04), social functioning AOR 1.02 (1.01-1.03), nausea and vomiting AOR 0.95 (0.93-0.98), pain AOR 0.95 (0.93-0.98), financial difficulty 0.97 (0.95-0.99), education AOR 4.3 (1.49-12.32), underweight AOR 0.45 (0.24-0.84),  > 5th cycle of chemotherapy AOR 4 (1.78-9.11), stage IV cancer AOR 0.21 (0.06-0.71), comorbidity AOR 0.28 (0.14-0.57), anxiety AOR 0.32 (0.12-0.84), and depression AOR 0.29 (0.13-0.63) were all significantly associated with QoL in multivariable logistic regression. Conclusion Adult cancer patients receiving chemotherapy in the Amhara region had a poor QoL. Emotional functioning, social functioning, nausea and vomiting, pain, financial difficulty, education, body mass index, cancer stage, chemotherapy cycle, comorbidity, anxiety, and depression all had association with QoL. To improve the QoL of cancer patients, QoL assessments, proper symptom management, nutritional support, and integration of psycho-oncology treatment should be considered.